Assessment of coastal resort development - Ladki, Said M. (2013)
This research investigates the relationships between illegally built resorts along Lebanon’s shoreline and beach goers’ right to access public beaches for free. The study was conducted by students at the Lebanese American University. Sample (n = 255) participants agreed to participate in this study. Pearson correlation and stepwise regression analysis results indicated significant relationships (p ≤ 0.05). Five hypotheses were tested, and four of which were accepted. The development of free public beaches is undoubtedly correlated with the illegally existing resorts along the coast. If illegally built resorts were to be legalized, communities may have free access to developed public beaches. The purpose of this research is to investigate the relationships between illegally built resorts along Lebanon’s shoreline and beach goers’ right to access public beaches for free. Beach goers’ opinions and attitudes towards public beaches are also investigated.